Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Hasil Belajar Pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Siswa Kelas IV SDN Cupak - Exela Nurfadilah; Meldi Ade Kurnia Yusri (Universitas Negeri Padang, 2022)
Schools have a significant position in the smooth process of education. At this time, education providers are increasingly aware of the meaning of media that supports education. Learning by using interactive media can be used as an alternative source to reduce student saturation in the educational process. especially can be used when science education at the SDN Cupak level. Therefore, the case studied in this study is